Raw Material Supply Control Analysis with Ordinary Least Square Method and Economic Order Quantity (Eoq) at Tandi's Bakery - Fatah, Abdul; Noorzaman, Sandi; Kartikasari, Maya Andini (Jurnal Logistik Indonesia, 2022)
MSMEsTandi's Bakery produces never stop every day. Therefore, inventory control has a very important position. At Tandi's bakery there are often stock outs and the determination of the Reorder Point is erratic. This study aims to determine the number of orders in the next 1 year using Ordinary Least Square (OLS) and to determine the optimal number of orders that must be issued by business actors, to find out when reorders must be made (ROP), and the application of the EOQ and OLS methods in Tandi's Bakery to optimize inventory costs. This type of research is descriptive in terms of data used primary and secondary data in the form of analysis related to the supply of raw materials for bread. The results showed that the sales of bread in the next 1 year amounted to87,868 pcs of bread according to the OLS method. The optimal purchase amount for Tandi's Bakery raw materials uses the EOQ method in the 2021/2022 period, namely 256 kg of flour, 55 kg of butter and 113 liters of liquid milk while in the previous period 291 kg of flour, 48 kg of butter and 69 liters of liquid milk. The frequency of orders using the EOQ method in the 2021/2022 period, namely 8 times flour, 4 times butter and 6 times liquid milk, while the order frequency for the previous period was 9 times flour, 4 times butter and 4 times liquid milk. The total inventory cost (TIC) using the EOQ method for the 2021/2022 period is as follows: Flour Rp. 255,148, Butter Rp. 135,417 and liquid milk of Rp. 174,006 while the previous period, namely flour, amounted to Rp. 891,032, Butter Rp. 870,670, liquid milk of Rp. 869,954. The exact time to reorder the reorder point (ROP) according to the EOQ method in the 2021/2022 period is 74,909 kg of flour, 8,438 kg of butter and 22,476 liters of liquid milk. In the previous period flour 97.129 kg, butter 6.387 kg and liquid milk 8.998 liters.